2020
DOI: 10.1007/s43032-020-00393-2
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Growth Restriction: Does an Integrated Maternal Hemodynamic-Placental Model Fit Better?

Abstract: In recent years, a growing interest has arisen regarding the possible relationship between adverse pregnancy outcomes (APOs) and inadequate maternal hemodynamic adaptations to the pregnancy. A possible association between “placental syndromes,” such as preeclampsia (PE) and fetal growth restriction (FGR), and subsequent maternal cardiovascular diseases (CVD) later in life has been reported. The two subtypes of FGR show different pathogenetic and clinical features. Defective placentation, due to a poor trophobl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 107 publications
(138 reference statements)
2
30
0
2
Order By: Relevance
“…Because of the decrease of placental blood supply and the aggravation of placental villus hypoxia and ischemia, the intake of nutrients and oxygen by the fetus decreases, which had adverse effects on the growth and development of the fetus. And it resulted in adverse outcomes such as FGR, fetal distress, hypoxia asphyxia and even death[ 41 , 42 ]. Lisonkovas et al [ 43 ] analyzed the clinical data of singleton pregnancies in 45,668 women and found that early-onset preeclampsia was associated with a significantly higher risk of adverse birth outcomes than late-onset preeclampsia.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the decrease of placental blood supply and the aggravation of placental villus hypoxia and ischemia, the intake of nutrients and oxygen by the fetus decreases, which had adverse effects on the growth and development of the fetus. And it resulted in adverse outcomes such as FGR, fetal distress, hypoxia asphyxia and even death[ 41 , 42 ]. Lisonkovas et al [ 43 ] analyzed the clinical data of singleton pregnancies in 45,668 women and found that early-onset preeclampsia was associated with a significantly higher risk of adverse birth outcomes than late-onset preeclampsia.…”
Section: Discussionmentioning
confidence: 99%
“…This information is not only useful for the diagnosis of FGR but can also be of value from the first trimester onward before poor fetal growth is evident ( 29 , 45 , 132 ). This opens perspectives toward the implementation of maternal hemodynamics parameters into current screening programs for FGR ( 7 , 133 ). Preliminary, though promising, data on the reduction of FGR have been reported on the supplementation of the screen positive high-risk group with antiplatelet therapy ( 134 , 135 ) and/or the antioxidants lycopene or L-Arginin ( 136 ).…”
Section: Clinical Implications Of Maternal Low Volume Circulation In ...mentioning
confidence: 97%
“…In recent years, however, the focus of research into the origins of gestational hypertensive disorders with or without FGR has shifted from the placenta to maternal cardiovascular dysfunction, present before conception or developing during the earliest stages of placentation ( 3 , 4 ). The interplay between maternal hemodynamics and the placentation process explains the two hemodynamic phenotypes of PE – one with high cardiac output (CO) and low vascular resistance and another with low CO and high vascular resistance – ( 5 , 6 ), as well as FGR ( 7 ), and also links maternal low CO to fetal increased umbilical and reduced cerebral Doppler impedance ( 8 ). Next to this, suboptimal plasma volume expansion is considered an intrinsic pathophysiologic feature of PE with FGR ( 9 ), and maternal normotensive low volume circulation has been associated with neonatal birthweight of <10th percentile ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, pregnancy generates structural and functional changes in the cardiovascular system, such as increased left ventricular mass and aortic compliance [108]. A great number of studies have demonstrated the critical function of these changes for the physiological course of gestation and the association between suboptimal adaptations and obstetrical complications, such as preeclampsia and FGR [109][110][111].…”
Section: Adaptation To Pregnancymentioning
confidence: 99%